MODELLING OF TRACER TRANSPORT IN THE WHITE SEA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
We consider advection of floating passive tracer in the White Sea using a hydrodynamical model of sea circulation JASMINE. Simulations show that the Onezhskiy Bay is a hydrodynamical trap for tracers: concentration there decrease more slowly. Typical times needed to remove concentrated tracer completely from bays are estimated. General scheme of tracer advection is described.